Diacylglycerol Kinase Delta Promotes Lipogenesis() - Shulga, Yulia V. (2013)
We have studied the relationship between diacylglycerol kinase delta (DGKδ) and lipogenesis. There is a marked increase in the expression of DGKδ during the differentiation of 3T3-L1 cells to adipocytes, as well as in the synthesis of neutral and polar lipids. When 3T3-L1 undifferentiated fibroblasts are transfected to express DGKδ there is increased triglyceride synthesis without differentiation to adipocytes. Hence, expression of DGKδ promotes lipogenesis. Lipid synthesis is decreased in DGKδ knockout mouse embryo fibroblasts, especially for lipids with shorter acyl chains and limited unsaturation. This reduction occurs for both neutral and polar lipids. These findings suggest reduced de novo lipid synthesis. This is confirmed by measuring the incorporation of glycerol into polar and neutral lipids that is higher in the wild type cells than in the DGKδ knockouts. In comparison, there was no change in lipid synthesis in DGKε knockout mouse embryo fibroblasts. We also demonstrate that the DGKδ knockout cells had a lower expression of acetyl-CoA carboxylase and fatty acid synthase as well as a lower degree of activation by phosphorylation of ATP citrate lyase. These three enzymes are involved in the synthesis of long chain fatty acids. Our results demonstrate that DGKδ markedly increases lipid synthesis, at least in part as a result of promoting the de novo synthesis of fatty acids.